Female reproductive system of Amaranthus as the target for Agrobacterium-mediated transformation - Munusamy, Umaiyal; Abdullah, Siti Nor Akmar; Abdul Aziz, Maheran; Khaza'ai, Huzwah (Scientific Research Publishing, 2013)
Agrobacterium-mediated transformation through floral dip and rapid selection process after transgenic event had become a preference as it will overcome the difficulties faced in tissue culturing procedures and lengthy time for screening transformed progenies. Therefore, in this study, three constructs, p5b5 (14,289 bp), p5d9 (15,330 bp) and p5f7 (15,380 bp) in pDRB6b vector which has hygromycin as a selectable marker gene were introduced individually into Agrobacterium tumefaciens strain (AGL1). The cell suspension was applied to Amaranthus inflorescence by drop-by-drop technique and was left to produce seeds (T1). The T1 seeds were germinated and grown to produce seedlings under non-sterile condition. Hygromycin selection on seedling cotyledon leaves results in identification of 12 putative transformants, three from p5b5, four from p5d9 and five from p5f7. All positive putative transformants that were selected at the first stage through hygromycin spraying showed positive result in leaf disk hygromycin assay and in a construct specific polymerase chain reaction-based assay. A ~750 bp amplified hygromycin gene was further verified through sequencing. Our results suggest that Amaranthus inflorescences were able to be transformed and the transformed progenies could be verified through a combination of simple and rapid methods.